MENCABAR PROBLEMATIKA SUMBER HUKUM ISLAM MUTTAFAQ SEBAGAI PIJAKAN DASAR MUJTAHID - Suhaimi, Suhaimi; Rozi, Mohammad Fahrur; Rifai, Achmad; Subroto, Gatot (Ulumuna: Jurnal Studi Keilsman, 2022)
The problem of the source of Islamic law is a very urgent matter to be discussed. Given in reality the source of Islamic law is a guideline for all Muslims. Therefore, it is necessary to have the validity of legal sources that have been agreed upon by the fuqaha' so that there are no fatal mistakes in practicing Islamic teachings. This paper will describe the sources of muttafaq Islamic law.